SURVEYING STUDENTS’ LEARNING PREFERENCES: MEMORIZING VS UNDERSTANDING CHEMISTRY ENGLISH TERMS - Keysha Rahma; Nazwa Syava; Wahyunengsih Wahyunengsih (JURNAL KIMIA SAINTEK DAN PENDIDIKAN, 2025)
English words appear everywhere in chemistry classes. Even so, knowing the words on paper does not mean that students feel comfortable using them. Quite a few students say they can memorize terms for an exam, but the meaning slips away when they need to explain or apply the terms in actual writing. This situation led the researcher to examine how chemistry students study these terms, whether they mostly memorize definitions or try to understand their meanings and how they are used. Fifty chemistry students took part in an online questionnaire with a five-point Likert response scale. This study employed a quantitative descriptive survey design, and the answers were summarized descriptively to identify which learning pattern stood out most. The results show that memorization remains prevalent, especially during exam periods. The highest mean score was 3.76 for the statement, “I often memorize chemistry terms without understanding their use.” Understanding concepts, however, seemed more helpful for long-term retention, with a mean score of 3.63. The strongest finding highlights the role of repeated exposure and contextual use of chemistry terms, which showed the highest mean score of 3.91. Based on these results, memorization helps in the short term, but its effect fades if the terms are not used again. When students understand a term and later encounter it repeatedly in class activities, the vocabulary tends to remain in their memory and feels easier to use naturally. These findings may contribute to the development of learning strategies that encourage continuous vocabulary practice, allowing terms to be applied not only in exams, but also in honest academic communication.